Building understandings of Māori and Samoan experiences of youth justice: Navigating beyond the limits of official statistics - Webb, Robert; Suaalii-Sauni, Tamasailau; Wright-Bardohl, Talia; Rauri, Juan (New Zealand Sociology, 2026)
This article draws upon a comparative sociological and criminological project into criminal justice processes and interactions with Māori and Samoan youth, whānau/aiga (family) and communities in three jurisdictions: Aotearoa/New Zealand, the United States and Australia. It outlines and then examines some of the limits of the official youth and juvenile justice statistics from these jurisdictions to foreground the discussion of the Indigenous research approaches used in our study. In particular, we explore the ways research on the understanding and experiences of the communities and the narratives of participants has built a critical understanding of youth justice that extends beyond the official state pictures of Māori and Samoan youth and offending.